Baseflow and water resilience variability in two water management units in southeastern Brazil - Santarosa, Lucas Vituri [UNESP]; Gastmans, Didier [UNESP]; Gilmore, Troy E.; Boll, Jan; Betancur, Sebastian Balbin [UNESP]; Gonçalves, Vitor Fidelis Monteiro (Taylor & Francis, 2022)
Changes in climate and water demand in densely populated regions increasingly affect hydrological systems, and, in turn, impact socioeconomic conditions. In this case study, we identify how the hydrogeological frameworks of two water resource management units, Tietê-Jacaré (TJ) and Piracicaba-Capivari-Jundiaí (PCJ) in Sao Paulo state (Brazil), control the baseflow processes and resilience in the face of streamflow fluctuations in response to anthropogenic activities and climate variation. The results reveal between 40% and 75% contributions of baseflow to total streamflow in basins overlying crystalline and sedimentary aquifers. The basins in PCJ which mostly overly crystalline aquifers, have shorter water residence times and greater dependence on surface water. Therefore, streamflow in the PCJ basins is vulnerable during the drought period and the management model affected the water resilience of the basins (transfer of water to Cantareira System). The TJ basins have greater streamflow contributions from aquifer discharge linked to the presence of important sedimentary aquifers, which improves resilience under changing rainfall patterns, these basins present a more stable situation of resilience. Ultimately, the two management units require different planning strategies with adaptive and dynamic actions to mitigate the social, economic, and environmental effects caused by the variability and reduction of water sources.
Keywords: baseflow; groundwater; hydrograph separation; resilience; Surface water